2008
DOI: 10.1598/jaal.52.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacies Go to School: Potholes and Possibilities

Abstract: Oftentimes it seems that education, as an institution, is populated by persons who work to preserve practices of the past and who do not depend upon or explore the advantages of digital literacies. Digital literacies, however, are here to stay—they are at the core of new literacies—and educators should consider how to best weave together old, new, and future literacies so that young people leave school literate in the ways of school and the ways of the world. يبدو كثيراً من الأحيان أنّ التعليم كمؤسّسة يؤهله ال… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 4 publications
1
26
0
2
Order By: Relevance
“…For example, researchers have found that the institutionalized structures of schools are often incompatible with the enactment of digital literacies [11]. Drayton, Falk, Stroud, Hobbs, and Hammerman [12] point to the importance of school cultural factors in affecting teacher uptake and integration of technology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers have found that the institutionalized structures of schools are often incompatible with the enactment of digital literacies [11]. Drayton, Falk, Stroud, Hobbs, and Hammerman [12] point to the importance of school cultural factors in affecting teacher uptake and integration of technology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, [18] indicates that digital literacy is the situation in which a person is encouraged by society to use his/her skills, capacities and strategies to present and comprehend the concept of various kinds of media, as well as efficiently apply digital tools and develop ideas and concepts.…”
Section: A Digital Literacymentioning
confidence: 99%
“…Furthermore, during the literature review, the researcher found that there is one main composition for digital literacy development that is regarded as a significant issue: cognitive skills. According to every composition of digital literacy development, students have to critically think, evaluate, decide and properly select information, which takes into account higher order thinking skills and this fits into a twenty-first-century skills perspective [18], [27], [28]. This also encompasses attitudes and perspectives concerning the ethical use of information.…”
Section: A Digital Literacymentioning
confidence: 99%
“…Researchers (Cervetti, Damico, & Pearson, 2006;Guthrie, 2004;Leu, Kinzer, Coiro, & Cammack, 2004;O'Brien & Scharber, 2008) have identified practices, skills, strategies, and dispositions that are required for digital reading, writing, collaborating, and learning. Additionally, researchers propose new teaching and learning models (Armstrong & Warlick, 2004;Leu, 2001;Richardson, 2010) that facilitate the development of those new literacies and enable students to participate in global learning experiences mediated by ICT's (information and communication technologies).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Researchers and theorists in the realm of new literacies (Cervetti, Damico, & Pearson, 2006;Leu, Kinzer, Coiro, & Cammack, 2004;O'Brien & Scharber, 2008) maintain that ICT's are central to literacy within a global community in the information age, that ICT's require new literacies, and that learning within those new literacies is often socially constructed. Among the new literacies that ICT's require is the ability to engage in threaded discussions and interactive chats in order to manage information (Guthrie, 2004) and share intellectual capital to solve important problems (Leu, Kinzer, Coiro, & Cammack, 2004).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%